1995
DOI: 10.1002/bies.950171206
|View full text |Cite
|
Sign up to set email alerts
|

DNA packaging and cutting by phage terminases: Control in phage T4 by a synaptic mechanism

Abstract: Phage DNA packaging occurs by DNA translocation into a prohead. Terminases are enzymes which initiate DNA packaging by cutting the DNA concatemer, and they are closely fitted structurally to the portal vertex of the prohead to form a 'packasome'. Analysis among a number of phages supports an active role of the terminases in coupling ATP hydrolysis to DNA translocation through the portal. In phage T4 the small terminase subunit promotes a sequence-specific terminase gene amplification within the chromosome. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 52 publications
(15 reference statements)
0
39
0
Order By: Relevance
“…These enzymes, which are required for packaging DNA (76), interact with each other (77). Other proteins, such as the ss DNA binding protein gp 32, or T4 gene 46-47 proteins, appear to be important in all recombination pathways, but different interactions with other proteins are important for their roles in different pathways.…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes, which are required for packaging DNA (76), interact with each other (77). Other proteins, such as the ss DNA binding protein gp 32, or T4 gene 46-47 proteins, appear to be important in all recombination pathways, but different interactions with other proteins are important for their roles in different pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmid GST-UL56C was generated by digestion of pRC/CMV-UL56 (7) and pGEX-5X-1 (Amersham Biosciences) as described previously (23). The 1.5-kb fragment encoding the carboxyl-terminal half of HCMV pUL56 (amino acids 446 -850) was ligated in-frame into pGEX-5X-1, yielding pGEX-UL56C.…”
Section: Methodsmentioning
confidence: 99%
“…The large subunit catalyzes the ATP-dependent translocation of genomic DNA into the bacteriophage procapsids and the small unit binds and cleaves concatenated DNA (21,22). Mutations in any of the encoding genes lead to an accumulation of empty procapsids (proheads) and DNA concatemers (23). Rao et al (24) demonstrated that the ATPase activity is associated with the large terminase subunit gp17 of bacteriophage T4.…”
mentioning
confidence: 99%
“…2B). These events should occur in adjacent terminal repetitions in a controlled manner such as the synaptic mechanism proposed for T4 (Black 1995). In f-29, DNA replication proceeds by a proteinpriming mechanism from either end of the linear molecule by strand displacement to generate mature molecules with gp3 covalently linked to the 5 0 -termini (Mellado et al 1980).…”
Section: Dna Processingmentioning
confidence: 99%